Reimagining Marginalized Foods : Global Processes, Local Places - Finnis, Elizabeth, 1976- (Book collections on Project MUSE., 2012)
This volume brings together ethnographically based anthropological analyses of shifting meanings and representations associated with the foods, ingredients, and cooking practices of marginalized and/or indigenous cultures. Contributors are particularly interested in how these foods intersect with politics, nationhood and governance, identity, authenticity, and conservation. The chapters cover diverse locales, issues, and foods ... A conceptual essay on food and social boundaries rounds out the collection. Throughout, the contributors address important questions ... (and) provide a thoughtful inquiry into what happens when food and culinary practices are moved from cultural physical margins, and how such movements can be shaped by- and employed in the pursuit of- political, social, and cultural goals. -- Book Jacket.